Analisis Penerapan Pendidikan Karakter Religius Pada Peserta Didik di Sekolah Dasar Pertiwi - Sri Wahyuni; Fitri Siti Sundari; Roy Efendi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
Character education is an important thing in the planning process to shape, direct and guide the behavior of students so that their behavior is in accordance with the norms that apply in carrying out their daily lives. One of the characteristics that must be possessed by students is a religious character which is closely related to individual attitudes and behavior with spiritual matters. The purpose of this study was to determine the application of religious character education to students, especially grade V students. This type of research used a qualitative research type with a descriptive approach. Methods of data collection using interview techniques, observation, and documentation. The results of this study indicate that there is an application of religious character education that is carried out in schools with religious activities called TPA such as students praying 5 times a day, reciting iqra/Al-quran, doing remembrance and prayer after prayer, memorizing letters, listening and recording cult messages Friday. Religious character in students can be formed gradually and continuously according to the willingness and ability of children, synergistic relationships between teachers and students, and collaboration with parents of Bogor Pertiwi Elementary School students.